2012
DOI: 10.1093/jrr/rrs024
|View full text |Cite
|
Sign up to set email alerts
|

Cell division cycle 25 homolog c effects on low-dose hyper-radiosensitivity and induced radioresistance at elevated dosage in A549 cells

Abstract: The underlying mechanisms behind both low-dose hyper-radiosensitivity (HRS) and induced radioresistance (IRR), generally occurring at elevated radiation levels, remain unclear; however, elucidation of the relationship between cell cycle division 25 homolog c (Cdc25c) phosphatase and HRS/IRR may provide important insights into this process. Two cell lines with disparate HRS status, A549 and SiHa cells, were selected as cell models for comparison of dose-dependent Cdc25c phosphatase expression subsequent to low-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 33 publications
2
6
0
Order By: Relevance
“…Activation of the ATM/Chk1 pathway could phosphorylate Cdc25c at Serine-216 (Ser-216) (Peng et al 1997;Zhao et al 2012;Xue et al 2016). The protein phosphatase Cdc25c regulates entry into mitosis by activating the Cdc2/CyclinB1 kinase complex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of the ATM/Chk1 pathway could phosphorylate Cdc25c at Serine-216 (Ser-216) (Peng et al 1997;Zhao et al 2012;Xue et al 2016). The protein phosphatase Cdc25c regulates entry into mitosis by activating the Cdc2/CyclinB1 kinase complex.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of Cdc25c was apparently higher in GSLCs than in GDCs and was almost unchanged after irradiation. Considering that Cdc25c is considered to be related to radioresistance (Zhao et al 2012;Li et al 2013), high expression of Cdc25c in GSLCs also indicates that GSLCs are more resistant to irradiation. Because the quantity of total Cdc25c protein in GSLCs is large, phosphorylated Cdc25c only accounts for a very small proportion of total protein: the remaining phosphatase Cdc25c remains sufficient to drive the cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al (2012) found that knockdown of Cdc25c induced a significantly more distinct hyperradiosensitivity and prevented the development of induced radioresistance. However, few studies have been carried out to explore the different roles of Cdc25a and Cdc25c in mediating the radioresistance through the activation of cell cycle checkpoint.…”
Section: Introductionmentioning
confidence: 93%
“…The transition from HRS to IRR is determined by cell-cycle related events involving the ataxia telangiectasiamutated (ATM)-dependent G2-phase cell-cycle checkpoint (Krueger et al 2007a(Krueger et al , 2010. Recently, a dose-dependent Cdc25c (cell division cycle 25C) phosphatase that effectively acts as an early G2-phase checkpoint regulator was implicated as being mechanistically important in the HRS to IRR transition in human A549 cells (Zhao et al 2012).…”
mentioning
confidence: 99%